Where are we now? Patterns of Māori and Pasifika enrolment in the Natural and Physical Science and Society and Culture fields in Aotearoa New Zealand. Issue 1 (2nd January 2021) - Naepi, Sereana; Wilson, Elizabeth; Lagos, Samantha; Manuela, Sam; McAllister, Tara G.; Kidman, Joanna; Theodore, Reremoana; Kokaua, Jesse
ABSTRACT: The continued underserving of Māori and Pasifika communities by New Zealand universities has resulted in the need to hold universities and the wider tertiary education system to account through widespread data analysis. This paper analyses Māori and Pasifika enrolment in the Society and Culture and Natural and Physical Sciences fields of Aotearoa New Zealand. The data indicate further targeted investment is needed in both fields, however, areas of investment differ between and within the fields. This paper also argues that the increasing use of Ministry of Education data to analyse current and past Māori and Pasifika inclusion in Aotearoa New Zealand universities means that this data needs to be transparent and reliable.